CHRONIC SMOKING AND ITS EFFECT ON ARTERIAL STIFFNESS - Binder, Svatopluk; Navratil, Kamil; Halek, Jan (Biomedical papers, 2008)
AIMS: The goal of this study was to investigate the effect of chronic smoking on arterial stiffness at a peripheral site using pulse wave analysis.METHODS: Forty two non-smokers (17 males, 25 females) of average age 20.2 extpm 1.3 year and forty five smokers (19 males, 26 females) of average age 24.3 extpm 2.4 year were included in the study. Four parameters, SI (stiffness index), RI (reflection index), CT (crest time) and IWD (interwave distance) were evaluated by means of an adapted device based on pletysmographic principles that transform volume changes to voltage changes.RESULTS: SI corresponding to pulse wave velocity was 0.64 m/s higher in smokers than in non-smokers (7.25 extpm 0.53 m/s versus 7.89 extpm 0.73 m/s, P < 0.001). RI was significantly higher in smokers (42.49 extpm 6.71 %, versus 35.46 extpm 0.06 %, P < 0.001) than in non-smokers. IWD for non-smokers was 8.01 extpm 0.13 %, in smokers we found a 16 % increase to 9.21 extpm 0.83 % (P < 0.001). We detected a small increase in CT in smokers compared to non-smokers (0.09 extpm 0.01 s versus 0.10 extpm 0.01 s, P < 0.005).CONCLUSIONS: Chronic tobacco smoking is associated with endothelial dysfunction. In smokers we found increased values for all assessed parameters. Our results suggest that the negative effect of cigarette smoking on the vascular system can be found even in young smokers who have been smoking for less than 10 years.
Keywords: Keywords: Pulsewave/Arterial stiff ness/Chronic smoking/Radial artery